Introduction of heuristic learning methods in the educational process of higher education (Pedagogy of Higher and Secondary Education, 2009)
The methods оf heuristic training for increase of educational process' efficiency in high school are analised in this article.
Keywords: heuristic; heuristic situation; heuristic method